2018
DOI: 10.1159/000488268
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Retinoic Acid Receptor Beta Promoter Methylation in Prostate Cancer: A Meta-Analysis

Abstract: Background/Aims: Retinoic acid receptor beta (RAR beta) is a retinoic acid receptor gene that has been shown to play key roles during multiple cancer processes, including cell proliferation, apoptosis, migration and invasion. Numerous studies have found that methylation of the RAR beta promoter contributed to the occurrence and development of malignant tumors. However, the connection between RAR beta promoter methylation and prostate cancer (PCa) remains unknown. This meta-analysis evaluated the clinical signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Data from Memorial Sloan Kettering Cancer Center [21] and TCGA Prostate Adenocarcinoma showed that RARγ was significantly and uniquely downregulated in prostate cancer compared with other cancers [22]. In addition, the RARβ promoter methylation status was higher in prostate cancer compared with nonmalignant tissues, suggesting reduced expression of RARβ in prostate cancer [23]. In LNCaP cells, RARγ signaling was shown to suppress AR signaling by competitive binding to AR-binding sites (Figure 1) [24,25].…”
Section: Subfamilies Of Nrsmentioning
confidence: 99%
“…Data from Memorial Sloan Kettering Cancer Center [21] and TCGA Prostate Adenocarcinoma showed that RARγ was significantly and uniquely downregulated in prostate cancer compared with other cancers [22]. In addition, the RARβ promoter methylation status was higher in prostate cancer compared with nonmalignant tissues, suggesting reduced expression of RARβ in prostate cancer [23]. In LNCaP cells, RARγ signaling was shown to suppress AR signaling by competitive binding to AR-binding sites (Figure 1) [24,25].…”
Section: Subfamilies Of Nrsmentioning
confidence: 99%
“…To dissect the impact of the miR-96 regulation of RARg further we examined how the correlations of each of the seven RARg network genes were altered by expression levels of miR-96. Specifically, we identified the significant correlations between each of the 19 seven RARg network genes (EIF4G2, ONECUT2, PRKAR1A, RARG, TACC1, YAP1, ZIC2 50 ) alongside FOXA1 with all RARg dependent genes in the upper (miR-96high, n=123) and lower (miR-96low, n=122) quartile miR-96 expression TCGA-PRAD tumors.…”
Section: The Mir-96 Governed Rarg Network Associates With Recurrent Pmentioning
confidence: 99%
“…There are three human RAR paralogs, namely RARa, RARb and RARg. In PCa, RARb appears to act as a tumor suppressor silenced by DNA methylation 10,19 . Curiously, while there are observed roles for RARg in prostatic development 44 , its role and regulatory functions in prostate cells and PCa remain enigmatic, as do its upstream control mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Reduced expression of RARB2 by genetic or epigenetic mechanisms is linked to many human cancers such as cervical [9,10], head and neck [11], non-small cell lung [12], prostate [13], bladder, brain, and breast cancers [4,14,15,16]. Knowledge of the DNA methylation status in the promoter regions of some candidate genes such as RARB2 may be useful for early detection, prognosis, and drug response prediction in breast cancer patients [6,17].…”
Section: Introductionmentioning
confidence: 99%